In vitro biocontrol potential of plant extract-based formulation against infection structures of Phytophthora infestans along with lower non-target effects - Penaud, Valentin; Alahmad, Abdelrahman; De Vrieze, Mout; Bouteiller, Mathilde; Eude, Miléna; Bernardon-Mery, Aude; Trinsoutrot-Gattin, Isabelle; Laval, Karine; Gauthier, Adrien (Frontiers in Microbiology, 2025)
Late blight, caused by Phytophthora infestans, is among the most destructive diseases affecting tomatoes and potatoes. The use of synthetic fungicides is becoming increasingly restricted due to the banning of several active ingredients for environmental and health reasons. Moreover, the rise of fungicide-resistant strains is compromising their effectiveness. Solutions for sustainable crop protection are thus urgently needed. Biocontrol products based on plant extracts appear to be a promising solution. This study aimed to evaluate in vitro inhibitory potential of a plant extract-based biocontrol product on the different stages of P. infestans lifecycle, including mycelial development and, formation and germination of infection structures (sporangia and zoospores). Non-target effects were also assessed using four fungi, three of which were isolated from the phyllosphere, and two ubiquitous bacteria. For this purpose, the formulated product (FV) and the plant extract at different concentrations (PE and CPE) were tested through bioassays. The results show that the mycelial growth of Phytophthora infestans was completely inhibited by the FV and less affected by the CPE. Infection structures were more sensitive to PE than mycelia, although FV was consistently the most effective inhibitor. Interestingly, at non-inhibitory doses, zoospore germination exhibited disturbances, such as an increase in abnormal germination phenotypes. Overall, PE showed significant inhibitory potential against the oomycete. FV exhibited a strong impact on mycelium, sporangia, and zoospores at very low concentrations (0.01–0.05%), suggesting an optimized inhibitory effect of PE. Non-target effects of FV on fungal and bacterial growth were observed only at concentrations substantially higher than those required to inhibit P. infestans in vitro. This study highlights the strong efficacy of the plant extract-based biocontrol product against the target oomycete, with minimal impact on non-target microorganisms. These findings support its potential as a promising anti-Phytophthora agent within integrated late blight management strategies.